Compact circularly polarized microstrip antennas for RFID reader applications - Boo, Yan Shan. (2009)
Microstrip antennas being low volume and conformable to host surfaces are replacing many conventional antennas. By using the appropriate feeding method and antenna design, the impedance bandwidth can be enhanced and the antenna size reduced to meet the desired device requirements. The main objective of the project is to fabricate a compact single feed circularly polarized (CP) microstrip antenna for RFID reader applications. A few research topics were undertaken. The first topic looks at the design of a broadband CP stacked microstrip antenna. Circular polarization is achieved by introducing an asymmetry and feeding the antenna at an angle of 45º using a coaxial probe. The proposed antenna was found to have a wide AR bandwidth of about 11.1% and a gain of more than 5.0 dBic for the broadband CP stacked microstrip antenna. The second topic looks at perturbations which are used to obtain CP radiation. The designs of three different compact CP microstrip antennas are discussed. From the study, the Y-slot configuration was able to achieve a lower resonating frequency compared to other designs with similar patch size. This translates to a significant reduction in size compared to the broadband stacked microstrip antenna. However, the drawbacks of this reduction in size led to reduced gain and a narrower AR bandwidth. The Y-slot antenna achieved a minimum S11 of -21.8 dB at 935 MHz and an AR bandwidth of only 1.3%. The gain obtained was more than -10dBic for the frequency range of 850 – 950 MHz. The last topic studies the effect of slits on the size of the antenna and the resonant frequency. The introduction of the slits provided a length reduction of about 6.9%. The proposed CP microstrip antenna is attractive for RFID reader applications which require compact size, good AR bandwidth and reasonable gain. All the antenna designs were built and simulated by the Zealand IE3D software.